Cytotoxicity Effect of Borassus flabellifer L. Seed Coat on Fibroblast - Risha Nadira Tyatana; Janti Sudiono (Indonesian Dental Association, 2021)
Introduction: Medicinal plants or herbal medicine are increasingly being developed and widely used by the community. Herbal medicine can be used as an alternative for the prevention and treatment of chronic, degenerative and cancer diseases. B. flabellifer L. is one of the palm tree which grow at tropical area such as Indonesia with popular name as ‘lontar’ or ‘siwalan’ B. flabellifer L. (lontar) seed coat was reported to have an antimycotic and antiproliferative activity against neoplastic cells. The use of alternative treatment is considered safe if its toxicity to normal cell is low. However there has been no research on cytotoxicity of B. flabellifer L. seed coat towards a normal cell. The normal cell that can be used for cytotoxicity tests were fibroblast. Objective: The aim of this study was to determine the cytotoxicity effect of B. flabellifer L. seed coat extract towards fibroblast. Method: The extract of B. flabellifer L. seed coat was done by maceration technique using 70% ethanol and then diluted to 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.56% concentrations. The MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] method was performed to evaluate fibroblast viability. The fibroblast were tested using various concentrations of B. flabellifer L. seed coat extract and the control groups consisting positive and negative control that were observed for 24 and 48 hours. The absorbance value was measured by microplate reader at 570 nm. Results: At 24 hours observation, the concentration of 1.56% was classified as mild toxic, the concencrations of 3.125%, 6.25%, 12.5% and 25% were classified as moderate, and the concentrarion of 50% as severe toxic. At 48 hours, the concentrations of 1.56%, 3.125%, 6.25% and 12.5% were classified as moderate while the concentrations of 25% and 50% as severe toxic. Conclusion: B. flabellifer L. seed coat extract has cytotoxicity effect towards fibroblast started from concentration of 1.56%.